ARTIFICIAL INTELLIGENCE IN DIGITAL MARKETING: GENERATION Z'S RECEPTION ANALYSIS OF FASHION AFFILIATE CONTENT ON SHOPEE - Maysa Maulida Kamal; Ade Kusuma (Adisam Publisher, 2026)
Technological advancements have continuously created innovations that make human life more efficient. Artificial Intelligence (AI), which was initially developed to assist humans in performing everyday tasks, has increasingly expanded into digital marketing, particularly through the emergence of AI-generated affiliate content used to promote fashion products on the Shopee e-commerce platform. This study aims to examine how Generation Z, as digital natives with a high level of digital literacy, receives and interprets the use of AI in promotional content. Employing a qualitative approach and Stuart Hall's Reception Analysis theory, this study explores how Generation Z's interpretations can be categorized into three audience positions: dominant-hegemonic, negotiated, and oppositional. Data were collected through in-depth interviews with five Generation Z informants. The findings reveal that although AI has introduced significant innovations and enhanced efficiency across various aspects of daily life, its application in digital promotional content has received criticism due to its perceived lack of authenticity. The characteristics of fashion products, which require detailed and accurate representations of texture, color, and size, make AI-generated virtual models unable to fully replace the representational role of real human models. Consequently, the findings indicate that none of the informants occupied the dominant-hegemonic position.